2004
DOI: 10.1007/s00114-004-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in metabolic competence of small and medium-sized synaptic mitochondria

Abstract: A computer-assisted morphometric investigation of cytochrome oxidase (COX) activity, selectively evidenced by preferential diaminobenzidine cytochemistry, has been carried out on synaptic mitochondria in the cerebellar cortex of adult and old rats. The ratio (R) of the area of the cytochemical precipitate (CPA) to the overall area of each mitochondrion (MA) was calculated. R refers to the fraction of the inner mitochondrial membrane actively involved in cellular respiration, thus its quantitative estimation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Moreover, by comparing old and late-adult controls we found that R was significantly higher in the old group only in the first two quartiles, while in the last two the values were similar. This implies that the average increase of R in old vs. late-adult controls relied on the smaller mitochondria (Bertoni-Freddari et al, 2005;Toescu, 2005). The maintenance of the metabolic efficiency in the largest mitochondria of late-adult and old control animals further support the view that the enlarging phenomenon may reflect a metabolic compensation rather than a symptom of unhealthy conditions.…”
Section: Effect Of Aging On Sdh-positive Mitochondriamentioning
confidence: 59%
“…Moreover, by comparing old and late-adult controls we found that R was significantly higher in the old group only in the first two quartiles, while in the last two the values were similar. This implies that the average increase of R in old vs. late-adult controls relied on the smaller mitochondria (Bertoni-Freddari et al, 2005;Toescu, 2005). The maintenance of the metabolic efficiency in the largest mitochondria of late-adult and old control animals further support the view that the enlarging phenomenon may reflect a metabolic compensation rather than a symptom of unhealthy conditions.…”
Section: Effect Of Aging On Sdh-positive Mitochondriamentioning
confidence: 59%
“…9 increasing severity [42] of AMD at the synaptic terminals of old rats [75] and in other adverse conditions where cells are exposed to large amounts of free radicals over an extended period [76,77]. The speculation is that numeric loss of mitochondria is due, in part, to impaired duplicative capacity of these organelles and that a shift in size compensates for numbers to keep volume density and area involved in cellular respiration constant during the lifespan of the individual [70,[78][79][80]. mtDNA is highly susceptible to oxidative stress and unlike nuclear DNA, mutations in mtDNA are not repaired.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio (R) reports on the fraction (%) of the inner mitochondrial membrane actively participating in the OX-PHOS process (i.e., the functional surface involved in energy providing mechanisms) and may be taken as a reliable quantitative estimation of the MMC of each organelle. [8][9][10] In addition to R, the following morphometric parameters of COX-positive mitochondria were measured: the mitochondrial area (MA), the overall area of the cytochemical precipitate (CPA), the mitochondrial longer diameter (Fmax), and the axial ratio (Feret ratio). The data obtained from each animal were ordered by increasing values of MA and then divided into four quartiles.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue samples (40-to 60-m thickness) were rinsed overnight in the buffer-sucrose solution and then incubated for 4 hours at 37°C in the dark. [8][9][10][11][12] Postfixation in osmium tetroxide was followed by embedding, sectioning, and contrasting procedures adopted in traditional electron microscopy. In the DAB-COX reaction, the electrons donated from DAB are transferred by COX from cytochrome c to oxygen to form water: in this electron translation, DAB is polymerized to an osmiophilic compound easily identifiable via light and electron microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation